(untitled) (Homoeopathy for All, 2024)
In Homoeopathic curriculum, Pharmacy is no doubt the most neglected subject, in spite of the fact that without understanding the principle and science behind preparation of homoeopathic medicines, it is not possible to get good medicine and it is also not very difficult to understand that if the physicians do not get quality medicine, all their effort of treating a patient will fail. Medicines are regarded as weapons in the hand of the physicians and if the weapon is blunt how they can fight successfully against diseases. Dr. Hahnemann advocated that medicines should be prepared by the physicians themselves so that they get the best quality weapon to fight against the ailments, but under the current socio-economic condition it is not practical for the physicians to prepare medicines themselves for treatment and they are required to depend on the pharmaceutical manufacturers for getting good quality medicines. Here the question arises if the manufacturers, even after employing BHMS qualified physicians for production of medicines, are able to produce quality homoeopathic medicines, do they understand the science of making medicine or they are just doing all these things mechanically.